Синтез и идентификация лактида и гликолида; Перспективы развития фундаментальных наук - Поздняков М. А.; Лыткина Д. Н.; Зенкова Е. В.; Ботвин В. В. Владимир Викторович; Филимошкин А. Г. Анатолий Георгиевич (Химия, 2013)
Заглавие с экрана